2022
DOI: 10.1177/15500594221128713
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cross Frequency Coupling of Brain Electroencephalographic Oscillations Related to Visual Oddball Task in Parkinson's Disease with Mild Cognitive Impairment

Abstract: Parkinson's disease (PD) is a movement disorder caused by degeneration in dopaminergic neurons. During the disease course, most of PD patients develop mild cognitive impairment (PDMCI) and dementia, especially affecting frontal executive functions. In this study, we tested the hypothesis that PDMCI patients may be characterized by abnormal neurophysiological oscillatory mechanisms coupling frontal and posterior cortical areas during cognitive information processing. To test this hypothesis, event-related EEG o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…PD-MCI patients compared to HCs were characterized by more frequent posterior topography of the δ-θ phase-amplitude coupling (PAC) and reversed δ-low frequency α PAC direction, i.e., posterior-to-anterior rather than anterior-to-posterior. This suggested that they showed abnormal neurophysiological oscillatory mechanisms mainly led by δ frequencies underpinning FC from frontal to parietal cortical areas [ 309 ].…”
Section: Neurophysiological Studies In Pd-cimentioning
confidence: 99%
“…PD-MCI patients compared to HCs were characterized by more frequent posterior topography of the δ-θ phase-amplitude coupling (PAC) and reversed δ-low frequency α PAC direction, i.e., posterior-to-anterior rather than anterior-to-posterior. This suggested that they showed abnormal neurophysiological oscillatory mechanisms mainly led by δ frequencies underpinning FC from frontal to parietal cortical areas [ 309 ].…”
Section: Neurophysiological Studies In Pd-cimentioning
confidence: 99%
“…It can increase neural information flow and improve the behavioral performance of actions controlled by distant neural populations [ 40 ]. Abnormalities in PAC have been connected to disruptions in higher-order cognitive processes such as alpha–gamma PAC decrease, which was detected in Alzheimer’s dementia patients in comparison to healthy controls [ 46 ], while topographical changes in delta–theta PAC were observed in PD patients with mild cognitive impairment during a visual oddball task [ 47 ]. Apart from its crucial role in higher-order cognitive processes [ 20 ], a significant impact of PAC can be attributed to coordinating neural populations responsible for movement execution [ 15 ].…”
Section: Introductionmentioning
confidence: 99%